Mapping the Research Footprint of Women in Computer Science and Engineering at IITs: A Decade of Bibliometric Insights (2014-2023) - Dey, Kishore (Information Research Communications, 2025)
Aim/Background This study investigates the research contributions of female faculty in Computer Science and Engineering (CSE) departments across 23 Indian Institutes of Technology (IITs) over the past decade. The objective is to map their research footprint and assess gender representation through bibliometric and scientometric analysis. Methodology Data on female faculty members were collected from the official websites of all IITs as of August 2024. Publication records from 2014 to 2023 were retrieved from the Scopus database. A total of 1,738 publications authored by female faculty were analyzed and visualized using Bibliometrix (R package), VOSviewer, and Microsoft Excel. The analysis included publication trends, top authors and sources, keyword analysis, and co-authorship patterns. Results Out of the total faculty analyzed, 12.48% were female, contributing to 11.72% of the publications. IIT Patna recorded the highest average research output and the most publications in 2023. Dr. Sriparna Saha (IIT Patna) was identified as the most prolific author. Lecture Notes in Computer Science (Springer Verlag) emerged as the most frequent publication source, with deep learning as the top trending keyword. The majority of contributors held Assistant Professor positions, and most publications were in the form of conference papers. Conclusion The findings highlight a notable gender disparity in research output and faculty representation in CSE departments of IITs. While there are standout individuals and institutions, overall female research participation remains limited. The study underscores the need for policy interventions, inclusive hiring, and stronger mentorship programs to promote gender equity in India’s premier engineering institutions.
Keywords: Bibliometrics; Scientometrics; CSE; Gender; Faculty; IIT; Engineering; Computer Science; Women.